Untargeted lipidomics of ovine milk to analyse the influence of different diet regimens. Issue 3 (10th August 2021) - Manis, Cristina; Addis, Margherita; Sitzia, Maria; Scano, Paola; Garau, Viviana; Cabiddu, Andrea; Caredda, Marco; Pirisi, Antonio; Pulina, Antonio; Roggero, Pierpaolo; Caboni, Pierluigi
Abstract: In this work we report a lipidomics approach to study the effects of two diet systems on the composition of ovine milk. Milk from two groups of Sarda sheep grazing on 40% (P40) and 60% (P60) of pasture were analyzed by a UHPLC-QTOF-MS analytical platform and data submitted to multivariate statistical analysis. Pairwise partial least square discriminant analysis of the lipid profile of the data was carried out to classify samples and to find discriminant lipids. The two dietary groups were characterized by differences in triacylglycerols, phosphocholines and phosphatidylethanolamines levels. Discriminants of the P40 group were TG and PC containing in their backbone saturated medium chain FA thus suggesting greater de novo fatty synthesis in the mammary gland. On the other hand, the P60 group was characterized by TG and PC formed by unsaturated long chain FA originating from the diet or from lipid mobilization.